(untitled) - Clements, Andrew; 1949-; Bynum, Janie (New York, 2004)
Slippers the puppy loves each of the four people who share his home.
Keywords: Fiction; Dwellings; Fiction; Human-animal relationships; Infancy; Fiction; Animals; Dogs; Juvenile fiction; Dogs; Fiction